2009
DOI: 10.1007/s10571-009-9462-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Novel Synthetic Derivatives of Carnosine

Abstract: Two novel derivatives of carnosine--(S)-trolox-L-carnosine (STC) and (R)-trolox-L-carnosine (RTC) are characterized in terms of their antioxidant and membrane-stabilizing activities as well as their resistance to serum carnosinase. STC and RTC were synthesized by N-acylation of L-carnosine with (S)- and (R)-trolox, respectively. STC and RTC were found to react more efficiently with 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) and protect serum lipoproteins from Fe(2+)-induced oxidation more successfully than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 27 publications
0
17
0
4
Order By: Relevance
“…We also examined carnosine as a positive control. Previous studies have demonstrated carnosine is significant antioxidant and anti-ischemic propertied in the brain (Stvolinsky and Dobrota, 2000;Dobrota et al, 2005;Stvolinsky et al, 2010) and also able to protect human neuroblastoma SH-SY5Y cells against OGD. In this evaluation, protective effects of compounds 1-3 against ischemic-like OGD were 3.6, 2.9 and 2.3 times more effective than carnosine, respectively (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined carnosine as a positive control. Previous studies have demonstrated carnosine is significant antioxidant and anti-ischemic propertied in the brain (Stvolinsky and Dobrota, 2000;Dobrota et al, 2005;Stvolinsky et al, 2010) and also able to protect human neuroblastoma SH-SY5Y cells against OGD. In this evaluation, protective effects of compounds 1-3 against ischemic-like OGD were 3.6, 2.9 and 2.3 times more effective than carnosine, respectively (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…The analogs modified in the amino group also include cyclodextrin derivatives (Amorini et al 2007), glycoside analogs (Lanza et al 2011) and Trolox modified derivatives (Stvolinsky et al 2010). These compounds are stable in human plasma, but the large (and stable) modifications in the N-terminus prevent the carbonyl scavenging and indeed these compounds have been designed mainly as radical scavengers and/or metal chelators.…”
Section: Carnosine Derivatives: Improving Oral Bioavailability and DImentioning
confidence: 99%
“…STC and RTC were concluded to demonstrate higher antioxidant capacity and better ability to prevent cerebellar neurons from ROS accumulation than their precursors, carnosine and trolox (Reviewed in Ref. [382]). Overall, natural low molecular mass antioxidant peptidomimetics add significantly to the defense provided by the enzymes superoxide dismutase, catalase and glutathione peroxidases [371,372].…”
Section: The Role Of Carnosine N-acetyl-carnosine and Carcinine Natumentioning
confidence: 99%